The Importance of How to Have A Successful Negotiation in Business - Luita Yusniawati Dratistiana (Swara Patra, 2018)
Negotiation is aimed to have one agreement with mutual achievement and no party gets lose. In business, negotiation skills are important in both informal day-to-day interactions and formal transactions such as negotiating conditions of sale, lease, service delivery, and other legal contracts even to government institution. Negotiating requires give and take. You should aim to create a courteous and constructive interaction that is a win-win for both parties. Ideally a successful negotiation is where you can make concessions that mean little to you, while giving something to the other party that means a lot to them. Your approach should foster goodwill, regardless of the differences in party interests and follow stages of negotiation to achieve a desirable outcome. Thus, there two famous approaches in negotiation which one of them is preferably choosen to fnd a solution to their differences that results in both sides being satisfed. Moreover, one psychological technique to support the udnerstanding of win – win approache is transactional analysis. A good negotiation leaves each party satisfed and ready to do business with each other again.